1993
DOI: 10.2190/vlyl-gvwl-nmfy-rjgk
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Autobiographical Memories in Depressed and Nondepressed Elderly Individuals

Abstract: An autobiographical memory task was used to study memory processes and depression in elderly individuals. Twenty-seven nondepressed and twenty-seven depressed elderly participants recalled thirty memories. Each memory was self-rated for happiness versus sadness and the degree of importance of the event at the time the event occurred (i.e., "then") and looking back on the event ("now"). Nondepressed participants perceived greater positive change in affective tone between "then" and "now" ratings. Depressed part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Autobiographical memory was more systematically sampled by randomly assigning these cues to childhood or recent periods in the participants' lives (Chew, 1979; see also Kihlstrom et al, 1988). In order to track changes in the affective valences of the memories over time (and thus obtain information about how memory retrieval might be affected by affect regulation), participants rated how they perceived the events they recalled now and also from the perspective of when the events actually occurred (Holmes, 1970;Yang & Rehm, 1993). As an additional measure of mood-congruency, we recorded response latencies in the cued-recall task (Clark & Teasdale, 1982;Lloyd & Lishman, 1975;MacLeod, Andersen, & Davies, 1994;Teasdale & Fogarty, 1979;Teasdale & Taylor, 1981).…”
mentioning
confidence: 99%
“…Autobiographical memory was more systematically sampled by randomly assigning these cues to childhood or recent periods in the participants' lives (Chew, 1979; see also Kihlstrom et al, 1988). In order to track changes in the affective valences of the memories over time (and thus obtain information about how memory retrieval might be affected by affect regulation), participants rated how they perceived the events they recalled now and also from the perspective of when the events actually occurred (Holmes, 1970;Yang & Rehm, 1993). As an additional measure of mood-congruency, we recorded response latencies in the cued-recall task (Clark & Teasdale, 1982;Lloyd & Lishman, 1975;MacLeod, Andersen, & Davies, 1994;Teasdale & Fogarty, 1979;Teasdale & Taylor, 1981).…”
mentioning
confidence: 99%
“…This means that as people grow older they experience fewer negative emotions. This positivity bias in memory appears to be a significant factor that contributes to the increase in positive emotion observed in older people (Pasupathi & Carstensen, 2003;Yang & Rehm, 1993).…”
Section: Discussionmentioning
confidence: 94%
“…Martin and Smyer (1990) asked participants to report about life events that had occurred at different times in their life span and found that the ratio of positive and negative events was 1.6, which means that for each 10 negative events there were 16 positive events. In a study where depressed and nondepressed participants were asked to retrieve 30 memories, all participants recalled more positive than negative memories (Yang & Rehm, 1993). Using a diary self-report memory method, Thompson (1998) found a small effect of pleasantness such that positive events were remembered slightly better than negative events.…”
Section: Affective Valence Of Life Eventsmentioning
confidence: 99%